Treating Arterial Stiffness in Young and Elderly Patients with the Metabolic Syndrome - Tziomalos, Konstantinos; G. Athyros, Vasilios; Karagiannis, Asterios (Current Pharmaceutical Design, 2014)
Arterial stiffness is independently associated with increased cardiovascular risk in patients with cardiovascular risk factors and in the general population. Metabolic syndrome (MetS) is frequently characterized by increased arterial stiffness since all components of MetS are implicated in the pathogenesis of arterial stiffness. We review the management of arterial stiffness in patients with MetS. Several small, short-term studies showed that lifestyle changes, antidiabetic, antihypertensive and lipid-lowering agents improve arterial elasticity. However, differences appear to exist between different classes of agents, with statins and inhibitors of the renin-angiotensinaldosterone system having the more favorable effects on arterial stiffness. A multifactorial approach appears to be the optimal management of increased arterial stiffness in patients with MetS.
Keywords: statins